What Are the Characteristics of Papillary Thyroid Microcarcinoma Prone to High-Volume Lateral Lymph Node Metastasis? - An Analysis of 2981 Consecutive Cases. Issue 7 (14th July 2022) - Gao, Luying; Li, Xiaoyi; Liu, Chunhao; Liu, Ruifeng; Shi, Xinlong; Ma, Liyuan; Zhao, Hao; Xia, Yu; Jiang, Yuxin
Abstract: Purpose: To identify candidate factors for predicting high-volume lateral lymph node metastasis (LLNM) in papillary thyroid microcarcinoma (PTMC). Methods: We retrospectively studied 2981 patients with PTMC who underwent thyroidectomy from 2013 to 2016. LLNM was identified by histopathology. Patients with different LLNM statuses were compared according to clinical, sonographic and pathological parameters. A multivariate logistic model was established to predict high-volume LLNM (number of metastatic lymph nodes >5). Results: High-volume LLNM of PTMC was independently associated with age < 40 years (OR = 1.791, P = 0.023), male sex (OR = 2.401, p  = 0.001), tumor size > 0.5 cm (OR = 4.839, p  < 0.001), extrathyroidal extension (OR = 2.097, p  = 0.007) and microcalcification (OR = 2.894, p  = 0.002). These five factors were incorporated together to develop a multivariate analysis, which showed good predictive ability (AUC = 0.78, 95% CI 0.72–0.83), with a sensitivity of 80.0% and a specificity of 61.4%. Moreover, more level II or V lateral regions were involved in patients with high-volume LLNM than in those with small-volume LLNM (69.2% vs. 25.0%, p  < 0.001; 10.8% vs. 4.7%, p  < 0.001). Conclusion: Multilevel LLNM tended to be more common in patients with PTMC who had high-volume LLNM. The high-volume LLNM rates of patients with PTMC with age < 40 years, male sex, tumor size > 0.5 cm, extrathyroidal extension and microcalcification were relatively higher than those without. These findings may be useful for identifying patients at higher high-volume LLNM risk who may require more aggressive treatment or intensive follow-up management.